Analyzing team effectiveness (TE) as a part of effective team management of GTZ Dhaka (Bangladesh) - Karim, Iftekhar -Ul (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.